Implementasi Aplikasi Pembelajaran Matematika Bangun Datar Bagi Siswa Sekolah Dasar Berbasis Android - Sarwati Rahayu; Vera Yunita; Umniy Salamah (Sekolah Tinggi Teknik - PLN, 2017)
Mathematics is the study of quantity, structure, geometry, and changes to a number. Math comes from the Greek, which Mathematikos which means an exact science. In the Dutch language of mathematics called as Wiskunde which means the science of learning. Mathematics is a science that is widely used in everyday life. Either generally or specifically. In general, mathematics is used in the trade transaction, carpentry and others. Almost every aspect of the life of mathematics can be applied. Therefore mathematics dubbed as the queen of all sciences. Math also has many advantages over other sciences. In addition to its flexible and dynamic, mathematics can always keep pace with the times. Especially in the present when everything can be done with a computer. Mathematics became one language programs effectively and efficiently. Mathematics is a compulsory subject for primary school students. Elementary school students often have difficulty in studying mathematics, especially in memorizing formulas. The material presented is usually in the form of a conventional, such as textbooks. In Mathematics Learning Application Geometry Two Dimensional Based Android, automatically the application can be run through the medium of mobile phones. This learning app designed using object-oriented modeling, using UML diagrams such, Use Case diagram, activity diagram, sequence diagram and Class diagram. Applications are also made using the programming language Java (J2ME)